Influencia de la densidad de corriente y peróxido de hidrógeno en la remoción de color de efluentes de recurtido mediante electrocoagulación - Castañeda Silvestre, Marvin Alessandro (2019)
In the present investigation, the influence of current density and hydrogen peroxide on the removal of color from the retanned effluent of the Ecological Tannery of the North was studied through the electrocoagulation process. For this process, a batch reactor of 1.8 L capacity and four electrodes was used, two asanode and the other two as cathode. Design parameters such as reactor volume, electrode dimensions have been defined by background. For the tests, the current density and the concentration of hydrogen peroxide were controlled simultaneously in the electrocoagulation process. From the above it was obtained that at a current density of 614.75 A/m2 and a hydrogen peroxide concentration of 700 ppm, a color removal of 83.80% was achieved in the first 30 minutes